Genetic diversity in seedling populations of Dipterocarpus gracilis in Kecubung Ulolanang Nature Conservation Reserve, Indonesia - Nesty Pratiwi Romadini; Sapto Indrioko; Widiyatno WIDIYATNO; Eny Faridah; Yeni Widyana Nurchahyani Ratnaningrum (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Romadini NP, Indrioko S, Widiyatno, Faridah E, Ratnaningrum YWN. 2021. Genetic diversity in seedling populations of Dipterocarpus gracilis in Kecubung Ulolanang Nature Conservation Reserve, Indonesia. Biodiversitas 22: 1138-1145. Dipterocarpus gracilis Blume is one of the native Dipterocarpus species in Java Island, Indonesia. It has commercial value as timber (wood) and non-timber forest products (oleoresin). This species has been considered vulnerable following the Red List of Threatened Species criteria by The International Union for Conservation of Nature (IUCN). We aimed to study the genetic diversity and genetic structure of seedlings as the natural regenerating population of Dipterocarpus gracilis Blume in The Kecubung Ulolanang Nature Conservation Reserve, Batang District, Central Java Province, Indonesia. The D. gracilis population in this area is distributed in four zones. We observed a total of 137 juvenile seedlings representing all the zones. Isozyme markers detected the genetic diversity of D. gracilis by peroxidase (PRX), esterase (EST), and acid phosphatase (ACP) enzymes. The mean observed heterozygosity of all the zones was lower (HO=0.078) than expected heterozygosity (HE=0.203). Genetic depletion occurred because of genetic drifts and founder effects due to low parental diversity. The genetic structure of seedlings is similar to the consequence of inbreeding. We conclude that the genetic diversity of D. gracilis decreases when mature trees are reduced. This population has essential values ??in Java Island and should be a priority evaluation in the in-situ and ex-situ conservation of genetic resources.